Kulturanasan Promoting Historical Heritage and Culture Appreciation through the integration of the Estacion de Barasoain Y Malolos with the Malolos NSCR station. - Dayrit, Vincent P.
Kulturanasan generates a landscape proposal along the Malolos NSCR Station within Bulacan to help revive the historical heritage of Malolos and promote cultural appreciation. The thesis attempts to effectively adapt to the negative effects of urbanization that may be caused by the opening of the NSCR transport hub through an experiential network and plaza center celebrating the history and culture of city. The project aims to integrate mixed-use development within the delineation of the site, providing an immersive experience to users while improving upon pedestrian access, connectivity, wayfinding, and mass transportation. The thesis adapts a design proposal that utilizes the Cultural Intelligence Model and the 5Ds model, leveraging the Estacion de Barasoin as a cultural catalyst serving as a central network relative to the heritage properties of Malolos. Through stakeholder survey and key informant interview, the design integrated the city’s cultural properties of Malolos to the transit-oriented development, offering a balance between efficient and fast-moving spaces, and cultural landscapes. The thesis developed a cultural plaza development as a central hub to help the city of Malolos in properly maintaining its cultural navigation, promoting cultural appreciation and preserving its historical heritage. As a key component in urban planning, the introduction of experiential landscapes to transport hubs promoted mass transit and effective urban mobility while integrating culture into mixed transport systems.